Living in the slow or fast lane: cognitive phenotypes in honeybees - Tait, Catherine A., author; Naug, Dhruba, advisor; Hoke, Kim, committee member; Ode, Paul, committee member; Brockmann, Axel, committee member (Colorado State University. Libraries, 2021)
The evolution and maintenance of cognitive variation is a question of fundamental interest in animal behavior because differences in cognition are predicted to underlie differences in behavior. The correlation between behavioral and cognitive variation has largely been conceptualized in terms of the speed-accuracy trade-off driving alternative cognitive strategies where 'fast' individuals are superficial learners that make inaccurate, risk-prone decisions relative to 'slow' individuals. My research has explored the factors that select for different cognitive abilities across species and the mechanisms that maintain variation in cognitive ability within species. To address these questions, I have identified how individuals of four honeybee species (Apis mellifera, A. cerana, A. dorsata, A. florea) differ in performance on multiple cognitive tasks and explored how such variation translates to behavioral outcomes and is shaped by ecology. In chapter one, I tested for the presence of variation in two different learning abilities in honeybee foragers and whether any component of learning influenced wing damage, an indicator of survival. My results demonstrated considerable interindividual variation in different types of learning abilities such that landmark and olfactory learning were negatively correlated. Additionally, I found that olfactory learning was positively correlated with maneuverability performance during flight, a measure which in turn positively influenced wing damage, a proxy for survival. This experiment demonstrated that individuals differ considerably in how they perform on two cognitive tasks and that cognitive ability has important implications for behaviors associated with survival. This work was further explored in chapter 2, where I studied how differences in learning preference relate to decision making during foraging. I measured individual latency to learn on a solitary foraging task and latency to learn on a social foraging task and found that individuals that perform well in a solitary learning task perform poorly in a social learning task. These findings suggest that honeybees specialize in one type of learning strategy when making foraging decisions, and such differences may have important implications for how individuals provision their colony. The first two chapters focused on how differences in performance on cognitive tasks may represent a trade-off that correlates to different behaviors. In the latter half of my dissertation, I first used multiple cognitive traits to define a cognitive phenotype in an individual and then investigated how such differences might impact performance on multiple behaviors and life history traits to determine functional consequences of cognitive variation. I then expanded this research to determine how differences in ecology shape cognitive phenotypes. In chapter three, I tested for the presence of distinct cognitive phenotypes in A. mellifera foragers by measuring multiple cognitive traits and determining whether these traits covary to produce distinct slow and fast cognitive phenotypes. I then compared performance on multiple behavioral and life history tasks to see if there were functional differences between these cognitive types. My results indicate the presence of two cognitive phenotypes that meet the predictions of the speed-accuracy trade-off and that are conserved across colonies. Compared to slow bees, fast bees were described by high associative learning, high preference for novelty and high preference for variance, bees which also engage in more nursing behavior and transition to becoming a forager at an earlier age. In chapter four, which explored how ecological and life history differences shape cognitive phenotypes between closely related honeybee species, I tested for differences in the cognitive phenotype in four honeybee species, each of which occupied a unique ecological niche that was correlated to their position on the slow-fast life history axis. My results indicate that a set of cognitive traits consistently covary within each species, resulting in slow and fast cognitive phenotypes that meet the predictions of the speed-accuracy tradeoff. I also found that the four species do not align on a slow-fast cognitive axis due to known differences in their life history and nesting ecology. Rather, cognitive differences among the species appear correlated to their brain size, which may be driven by differences in foraging range. Taken together, this work indicates that cognitive variation at the individual level has important behavioral and life history outcomes that may impact how the individual interacts with their environment and how the colony performs. At the species level, cognitive variation appears to be driven by a complex relationship with the species unique environment as well as underlying trade-offs associated with costs of cognition.